Opieka stomatologiczna oraz problemy zdrowia jamy ustnej u pacjentów w Ośrodku Rehabilitacji i Leczenia Trądu w Puri (Indie) - doświadczenia własne* - GERRETH, KAROLINA (Annales Missiologici Posnanienses, 2010)
Most people in developing countries have little or no access to organized oral health care or to basic emergency dental treatment. The main reasons are lack of dentists and poor socio-economic status. Particularly access to dental health is characteristic of isolated groups such as, e.g., lepers’ colonies. The author presents her own observations gathered during two medical missions organized by the Redemptoris Missio Humanitarian Aid Foundation to the Karunalaya Leprosy Care Center in Puri, in 2001 and 2003. The paper describes the problems resulting from health status, methods of dental treatment and ways of teeth cleaning. The author’s experience shows that even if dental aid is rendered at irregular intervals it allows to treat successfully a relatively high number of patients. The poor appreciate any dental help, which, in turn, encourages the dentist to continue his/her efforts in the future.